DEVELOPING TEACHING MATERIALS IN INTEGRATED NATURAL SCIENCE CLASS BASED ON INQUIRY LABS TO IMPROVE STUDENTS’ SCIENCE LITERACY - Yusmanila Yusmanila (JURNAL TARBIYAH, 2021)
The low scientific literacy of Indonesian students indicates the low quality of science/science education. Reality on the ground in the science learning process is that teachers only use textbooks and have not developed inquiry labs-based teaching materials. The research objective is to develop an integrated science teaching material based on inquiry labs that is valid, practical, and effective. The type of research is research and development (r&d). The test was conducted in class VIIB of MTsN 6 Sijunjung. The instruments used are expert validation sheets and student questionnaires. The data analysis technique used in this research is qualitative and quantitative analysis. The results of the validation of teaching materials have an average value of 89, meaning are very valid. The average practicality test results for teaching materials are 84, meaning are very practical. The results of statistical tests on students' scientific literacy tests were effective in increasing students' scientific literation